Early Identification and Intervention of Underachievement among Gifted Students - Sovy, Rosiyatus; Ramanda, Peni; Ramdhan, Septi Nuririanti; Sarah , Siti; Amanina, Farah Ayu (IKIP Siliwangi, 2025)
This study aims to identify the underlying factors contributing to underachievement in gifted students and to formulate early intervention strategies that schools can implement. A qualitative case study approach focused on a high school student with strong academic potential who experienced a significant decline in academic performance, placing them at risk of not being promoted to the next grade. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that the main factors contributing to underachievement include a lack of interest in certain subjects, an unsupportive social environment, and unstable family dynamics caused by the absence of a father figure. The study concludes that early identification and collaborative interventions involving subject teachers, school counselors, and parents play a crucial role in helping gifted students regain their academic performance in line with their potential. The implications of this study serve as a reference for teachers in implementing early screening and targeted intervention programs for gifted students experiencing underachievement.